Development of Technopreneurship-Based E-Modules for Ethnochemistry, Redox, and Science Literacy - Yanti, Febri; Simangunsong, Anita Debora; Sitinjak, Erni Kusrini; Pane, Eva Pratiwi; Septiani, Nanda Teodora (Aptisi Transactions On Technopreneurship (ATT), 2025)
This research is very important to improve the quality of student learning, which is supported by good knowledge and a teaching process. It uses various sources and teaching materials presented interestingly so that students get various experiences in the field of chemistry as expected. By developing an Emodule based on ethnochemistry (culture related to chemistry), this study bridges the gap in existing teaching materials that lack cultural integration, which often hinders students engagement and scientific literacy development. The novelty of this research lies in the integration of local cultural practices, such as Batak culture, into redox chemistry learning, creating an innovative approach to enhance students scientific literacy. The method used in this study is a qualitative and quantitative approach, specifically employing a 4D model (define, design, development, dissemination) to develop and validate the module. The results show that the ethnochemistry based module teaching materials on redox material are the characteristics of effective modules, achieving validation scores of 3.45 from media experts and 3.37 from material experts, categorized as "very appropriate". Additionally, student responses to the E-Module were very positive, with an average score of 3.70, indicating its effectiveness in enhancing students understanding and engagement.